Potret Perilaku Menyimpang Masyarakat Urban Dalam Novel 24 Jam Bersama Gaspar Karya Sabda Armandio - Reddi Mardialis; Muhammad Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to describe: (1) the forms of urban deviant behavior in Sabda Armandio's novel 24 Jam Bersama Gaspar; (2) the causes of deviant behavior in Sabda Armandio's novel 24 Hours with Gaspar; and (3) the impact of deviant behavior deviating urban society in the novel 24 Hours with Gaspar by Sabda Armandio. The research data is in the form of words, phrases, clauses and sentences that indicate the forms, causes, and impacts of deviant behavior in the novel 24 Hours with Gaspar by Sabda Armandio. The research instrument was the author himself, with the help of another instrument in the form of a recording sheet. Data collection techniques include reading and understanding novels, conducting literature studies, determining the main characters, and finding and recording data related to research problems contained in the novel. data analysis techniques, namely, identifying and classifying data. Then interpret the data and conclude the data analysis. The results of the study stated that in the novel 24 Hours with Gaspar by Sabda Armandio, forms of deviant behavior were found, which included (1) robbing or stealing, (2) extramarital sex, and (3) skipping school. (4) fanaticism, (5) followers of false religious teachings, (6) disobedience to parents, and (7) pedophilia. in the novel 24 Hours with Gaspar Karya Sabda Armandio, four factors are found that cause deviant behavior, which include: (1) family disharmony; (2) the expression of disappointment; (3) economic necessity; (4) the influence of the environment and the mass media. In the novel 24 Hours with Gaspar by Sabda Armandio, two impacts of deviant behavior are found: (1) criminality and (2) the fading of values and norms.